THE EFFECT OF PRODUCT AND PACKAGING VARIATIONS ON PURCHASING DECISIONS - Mahira, Tengku Ismalia; Nurwani, Nurwani; Dharma, Budi (Jurnal Ekonomi dan Bisnis, 2024)
This study aims to explore the impact of product variations and packaging on purchasing decisions at Micro, Small and Medium Enterprises (MSMEs) "Sambalin Aja" in Medan City. The research method applied is a quantitative method with an associative approach. The results of the analysis show that partially, product variety (X1) does not have a significant influence on purchasing decisions, with a calculated t value (1.085) lower than the t table value (2.03452), and a significance value greater than 0.05 (0.286). Meanwhile, the packaging variable (X2) positively and significantly influences purchasing decisions, as evidenced by the t count (4.265) which exceeds the t table (2.03452), and a significance value of 0.000, with an unstandardized beta coefficient for the packing regression of 0.554. This finding indicates that the management of UMKM "Sambalin Aja" needs to pay special attention to the aspect of product packaging, along with increasing the variety of products that can be the choice of consumers. It is recommended that management re-analyze the competitiveness of packaging and product variations compared to competitors, to ensure optimal competitiveness in the market.